NRF2 Mediates Therapeutic Resistance to Chemoradiation in Colorectal Cancer through a Metabolic Switch - Séan M. O'Cathail; Chieh-Hsi Wu; Rachael Thomas; Maria A. Hawkins; Tim S. Maughan; Annabelle Lewis (MDPI AG, 2021)
Radiation resistance is a significant clinical problem in rectal cancer treatment, the mechanisms of which are poorly understood. NRF2 signalling is known to contribute to chemo/radioresistance in some cancers, but its role in therapeutic resistance in colorectal cancer (CRC) is unexplored. Using siRNA and CRiSPR/Cas9 isogenic CRC cell lines, we investigated the effect of the knockdown and upregulation of the NRF2 pathway on chemo-radiosensitivity. Poly (A) enriched RNA sequencing and geneset enrichment analysis (GSEA) were carried out on both sensitive and resistant cell models for mechanistic insights. Finally, a cohort of rectal patient samples was profiled to understand the clinical relevance of NRF2 signalling. Radioresistant cell lines were significantly radiosensitised by siRNA knockdown (SW1463, SER10 1.22, ANOVA p < 0.0001; HT55, SER10 1.17, ANOVA p < 0.01), but not the (already) radiosensitive HCT116. The constitutive activation of NRF2 via a CRISPR Cas9 NFE2L2 mutation, E79K, induced radioresistance in HCT116 (SER10 0.71, ANOVA, p < 0.0001). GSEA demonstrated significant opposing metabolic dependencies in NRF2 signalling, specifically, the downregulation of amino acid and protein synthesis with low levels of NRF2 and upregulation with over expression. In a clinical cohort of 127 rectal patients, using a validated mRNA signature, higher baseline NRF2 signalling was associated with incomplete responses to radiation higher final neoadjuvant rectal (NAR) score (OR 1.34, 95% C.I. 1.01-1.80, LRT p-value = 0.023), where high NAR indicates poor radiation response and poor long-term prognosis. This is the first demonstration of NRF2-mediated radiation resistance in colorectal cancer. NRF2 appears to regulate crucial metabolic pathways, which could be exploited for therapeutic interventions.